Perancangan produk fungsional berbahan limbah kayu sisa produksi tempat air kemasan gelas - Achmad Zainudin; Dwi Agus Susila (Institut Seni Indonesia Yogyakarta, 2021)
The initial idea of this research is to exploit the abundance of wood waste material in the form of coins which have almost the same size and thickness. This waste comes from the rest of the production of glass bottled water. One way to achieve this goal is by using horizontal and vertical lamination techniques with the addition of a turning process with the aim of being able to form and produce functions. Another goal is to apply the waste coin arrangement as a functional and decorative product design material. The design of this product with waste is used as a model for empowering the creative industry of the local crafts-producing community where glass mineral water is located in Sambeng Village, Kasiman District, Bojonegoro Regency, East Java. The design method used is the Design Thinking method. The output produced is in the form of functional and decorative product designs, such as stools, wall clocks, frames, candle holders, egg holders, menu boards, and placemats.